Measuring and Assessing Impacts of Fair Trade for All on farmers, farmworkers and the overall Fair Trade Market System (Brazil) - Rio, Martha del; González, Carolina; Sellitti, Stefania; Lundy, Mark M. (International Center for Tropical Agriculture, 2018)
Assess the impact of the selected FT4ALL coffee pilots. Analyze empowerment processes and changes overtime on Fair Trade Certified independent small-scale coffee producers. Identify the early effects of FT4ALL on the Fairtrade certified coffee market and assess the viability of the supply chain.